2012
DOI: 10.1128/iai.05904-11
|View full text |Cite
|
Sign up to set email alerts
|

Two Zinc Uptake Systems Contribute to the Full Virulence of Listeria monocytogenes during Growth In Vitro and In Vivo

Abstract: We report here the identification and characterization of two zinc uptake systems, ZurAM and ZinABC, in the intracellular pathogen Listeria monocytogenes. Transcription of both operons was zinc responsive and regulated by the zinc-sensing repressor Zur. Deletion of either zurAM or zinA had no detectable effect on growth in defined media, but a double zurAM zinA mutant was unable to grow in the absence of zinc supplementation. Deletion of zinA had no detectable effect on intracellular growth in HeLa epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 36 publications
0
66
0
Order By: Relevance
“…A few bacterial species have been reported to have more than one zinc uptake system (2). For example, deletion of either of the two zinc uptake systems in Listeria monocytogenes results in no detectable growth defect in zinc-limiting medium, but deletion of both systems results in severe growth defects in vitro and in vivo (17). For V. cholerae, Znu-ABC apparently plays a predominant role in zinc uptake in vitro, but in vivo both ZnuABC and ZrgABCDE are equally important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few bacterial species have been reported to have more than one zinc uptake system (2). For example, deletion of either of the two zinc uptake systems in Listeria monocytogenes results in no detectable growth defect in zinc-limiting medium, but deletion of both systems results in severe growth defects in vitro and in vivo (17). For V. cholerae, Znu-ABC apparently plays a predominant role in zinc uptake in vitro, but in vivo both ZnuABC and ZrgABCDE are equally important.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, many bacterial pathogens must be able to acquire zinc in order to cause disease. A number of pathogens, including E. coli, Haemophilus, Salmonella, Listeria, and Campylobacter, require the ZnuABC transporter system to colonize hosts (12)(13)(14)(15)(16)(17). However, it is less clear how another important pathogen, Vibrio cholerae, regulates its zinc homeostasis in different environmental niches and whether zinc uptake systems contribute to its pathogenesis.…”
mentioning
confidence: 99%
“…Zinc uptake systems are known to be important for virulence in many bacteria (59,60). However, in virulence assays using N. benthamiana as the host plant, growth either in LB (a zinc-replete condition) or in LB plus 0.5 mM EDTA (a zinc-depleted condition) had no effect on the virulence of A. tumefaciens mutant strains lacking zinc uptake genes compared to the wild type.…”
Section: Discussionmentioning
confidence: 98%
“…Listeria monocytogenes contains two zinc permease systems, ZurAM and ZinABC, which are regulated by Zur (60). The presence of two high-affinity zinc uptake systems helps these bacteria to survive in diverse zinc-limiting environments and during infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that recent studies have shown that the production of multiple proteins involved in zinc uptake is not limited to bacteria expressing ZinT. For example, Listeria monocytogenes expresses two ABC-type Zinc importers, both contributing to full virulence [47], while in Streptococcus pneumoniae the zinc importer AdcAII (a ZnuA homologue) can form a complex with the zinc-binding surface protein PhtD, suggesting that this interaction contributes to the efficiency of the zinc uptake mechanism [48].…”
Section: Discussionmentioning
confidence: 99%